(3GdJdNjU aj CUhd Gdabgs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf aUd ai MbjbI Gdabg hCUhd Gdabg , aEf bGd bGFd (B: (3eG MbjbI Gdabg ? bjd (B: (3Gdabg ai MbjbI GddZI gh GdYde s
(3BNQgG (B:s
(3hESJbUGA GdcdGe ai CWQGa gPg GdeSCdI jJYdb Haf GdcdGe , hajeG PcQfGg ZfjI Ef TGA Gddg YR hLd Je cJGH GdJdNjU s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeY GdQhVI HVhGMi UfYGA s
Keywords: (3Gdabg GdESdGejs